A juventude e as interações sociais: a influência do grupo de pares e a constituição da identidade dos jovens - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
This thesis "Youth and social interactions: the influence of the peer group and the establishment of the identity of the young" has as its central theme the anchoring of the young in the peer group and the establishment of their identity, bringing together the theoretical and conceptual elements and the empirical evidence aggregate in the research process. We articulate the itinerary of research, ongoing dialogue with the research object, setting as main objective to investigate the influence of peer groups on the behavior of young people, to identify the interactions of processes that subjects establish to seek recognition and belonging to the social group. As for his approach to research and qualitative, procedures and research techniques we adopt to build the knowledge on youth and the peer group followed the itinerary of literature, activities in the focus group and semi-structured interviews, and we use the observations and notes in a field book that collaborated with our thinking. We organize the material collected observing the content analysis method, considering four thematic categories that revealed the results of the investigation. The research findings are tentative, pointing to the understanding that the young man entered prepare their experiences in different social groups, and the youth group of great importance to acquire experiences. Moreover, young people are plural subject, experiencing the multiplicity of relationships, cultures and diversities, participating in interaction networks is a multifaceted social context.
Keywords: Interação social; Comportamento social; CIÊNCIAS HUMANAS: EDUCAÇÃO